2014
DOI: 10.1186/s13612-014-0025-4
|View full text |Cite
|
Sign up to set email alerts
|

Beyond positive and negative trait affect: Flourishing through music engagement

Abstract: Background: Mental health is not only the absence of mental illness, but also the presence of positive well-being. Music is often cited as an effective tool for regulating emotions and may also promote well-being because music facilitates one's ability to regulate the experience and expression of emotions. Methods: This study aimed to examine the pathways by which music use for cognitive and emotional regulation purposes may predict mental health outcomes, as measured by self-reports of well-being and negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 69 publications
2
13
0
1
Order By: Relevance
“…The study of strategies within musical affect regulation is especially challenging due to the unfitness of general affect regulation models to the case of music (Randall, Rickard, & Vella-Brodrick, 2014) and the difficulty in defining strategies and differentiating them from other concepts such as musical goals and tactics (Baltazar & Saarikallio, 2016). Studies differ in whether the strategy as a concept refers to processes identified in general affect regulation or processes encountered specifically in music, but overall, music has been reported to facilitate strategies such as reappraisal (Chin & Rickard, 2014a;Randall et al, 2014), entertainment/fun seeking (Gebhardt, Kunkel, & Von Georgi, 2014;Saarikallio & Erkkilä, 2007), relaxation (Van Goethem & Sloboda, 2011), revving up/ energizing (DeNora, 1999;Saarikallio, 2011), and finding solace (Saarikallio & Erkkilä, 2007) (see a complete compilation in Baltazar & Saarikallio, 2016). Recent work has also noted that different strategies have differing impacts on development, wellbeing, and psychological health (Carlson et al, 2015;Chin & Rickard, 2014a;Gebhardt et al, 2014;Marik & Stegemann, 2016;Schäfer & Sedlmeier, 2009;Thoma, Ryf, Mohiyeddini, Ehlert, & Nater, 2012;Thomson, Reece, & Di Benedetto, 2014).…”
Section: Research On Strategies and Mechanisms In The Context Of Musimentioning
confidence: 99%
“…The study of strategies within musical affect regulation is especially challenging due to the unfitness of general affect regulation models to the case of music (Randall, Rickard, & Vella-Brodrick, 2014) and the difficulty in defining strategies and differentiating them from other concepts such as musical goals and tactics (Baltazar & Saarikallio, 2016). Studies differ in whether the strategy as a concept refers to processes identified in general affect regulation or processes encountered specifically in music, but overall, music has been reported to facilitate strategies such as reappraisal (Chin & Rickard, 2014a;Randall et al, 2014), entertainment/fun seeking (Gebhardt, Kunkel, & Von Georgi, 2014;Saarikallio & Erkkilä, 2007), relaxation (Van Goethem & Sloboda, 2011), revving up/ energizing (DeNora, 1999;Saarikallio, 2011), and finding solace (Saarikallio & Erkkilä, 2007) (see a complete compilation in Baltazar & Saarikallio, 2016). Recent work has also noted that different strategies have differing impacts on development, wellbeing, and psychological health (Carlson et al, 2015;Chin & Rickard, 2014a;Gebhardt et al, 2014;Marik & Stegemann, 2016;Schäfer & Sedlmeier, 2009;Thoma, Ryf, Mohiyeddini, Ehlert, & Nater, 2012;Thomson, Reece, & Di Benedetto, 2014).…”
Section: Research On Strategies and Mechanisms In The Context Of Musimentioning
confidence: 99%
“…At the same time, there have been relatively few direct investigations of the relationship between self-reported functions of music listening and specific wellbeing outcomes (Laukka, 2007 ; Thoma et al, 2012 ; Chin and Rickard, 2014a , b ; Papinczak et al, 2015 ; Saarikallio et al, 2015 ; Randall and Rickard, 2017 ). The limited number of studies is perhaps due to the lack of suitable measures.…”
Section: Introductionmentioning
confidence: 99%
“…The limited number of studies is perhaps due to the lack of suitable measures. Some of these studies have used well-developed psychometric measures of FML (Chin and Rickard, 2014a , b ; Saarikallio et al, 2015 ), whereas other studies have used a limited number of researcher-selected lists of FML without carrying out further scale development or validation. This suggests that a new integrative measure of music listening functions that is psychometrically sound may be a useful addition to the emerging field of music, health, and wellbeing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), estudos compreensivos de como a música é criada, interpretada e experienciada, e estudos de como usamos a música e a importância que ela tem na vida de indivíduos. Estes estudos referem que a música é uma atividade de lazer com a capacidade de melhorar o bem-estar (RICKARD; MCFERRAN, 2012apud MACDONALD et al, 2012CHIN;RICKARD, 2014) e ter impacto sobre os sintomas de doença mental, como depressão e ansiedade (MARATOS et al, 2008;BRADT et al, 2011;SIEDLIECKI;GOOD, 2006 apud CHIN;RICKARD, 2014).…”
unclassified